Place Image, Quality Services, and Event Attachment in Sarawak: Moderating Role of Community Support in Economic Development - Abang Azlan, Mohamad; Lo, May Chiun; Wan Hashim, Wan Ibrahim; Chin, Ying Sin (Cognizant Communication Corporation, 2023)
Malaysia's event industry, notably in culturally diverse Sarawak, has thrived in recent years, becoming a significant economic driver. However, the COVID-19 pandemic severely disrupted the sector, resulting in event cancellations, economic losses, and reduced community engagement. This study investigates the role of event attachment in fostering local economic development in Sarawak. The research gathered data from 1265 diverse event attendees and employed WarpPLS 8.0 to analyse the proposed model. Findings highlighted the substantial impact of place image, service quality, and community support on event attachment and, subsequently, economic development. Notable events like the Rainforest World Music Festival and Sarawak Regatta are analysed. The study offers practical insights for event planners and policymakers to boost event attachment, emphasizing place image, quality services, and community support to drive economic development in Sarawak. This research highlights the pivotal role of event attachment in sustaining the region's economic growth.